2010
DOI: 10.1021/jo902394y
|View full text |Cite
|
Sign up to set email alerts
|

Brønsted Base-Catalyzed One-Pot Three-Component Biginelli-Type Reaction: An Efficient Synthesis of 4,5,6-Triaryl-3,4-dihydropyrimidin-2(1H)-one and Mechanistic Study

Abstract: An efficient one-pot synthesis of 4,5,6-triaryl-3,4-dihydropyrimidin-2(1H)-ones via a three-component Biginelli-type condensation of aldehyde, 2-phenylacetophenone, and urea/thiourea in the presence of a catalytic amount of t-BuOK (20 mol %) is described. The reactions proceeded efficiently at 70 degrees C to afford the desired products in moderate to good yields. Detailed mechanistic study shows that the Biginelli-type reaction using urea and thiourea proceeds through two totally different pathways. Enone 5 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
63
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(67 citation statements)
references
References 95 publications
0
63
0
4
Order By: Relevance
“…Very recently, Z-L. Shen and co-workers [53] reported that t-BuOK catalyzes one-pot synthesis of DHPMs via a Biginelli-type condensation from aldehydes and 2-phenylacetophenone.…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, Z-L. Shen and co-workers [53] reported that t-BuOK catalyzes one-pot synthesis of DHPMs via a Biginelli-type condensation from aldehydes and 2-phenylacetophenone.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, in the process of designing new MCRs yielding DHPMs, the utilization of new C5–C6 fragment donors constituted the major strategy. Representative new C5–C6 building blocks used in the multicomponent synthesis of DHPMs are 2-oxosuccinic acid [27], acetylaldehydes [28], cyclic and acyclic ketones [2931], β-oxo dithioesters [32], diketenes [33] and enaminones [34]. On the other hand, as frequently utilized building blocks in organic synthesis, alkynes have been known to possess versatile reactivity in the synthesis of small molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Algumas dessas modificações incluem o uso de ácido de Lewis como catalisador, a ausência de solventes, a utilização de micro-ondas e, mais recentemente, o emprego de condições básicas. 12,13 O esforço para o desenvolvimento de metodologias mais eficientes para a síntese de 1 deve-se ao fato desta classe de compostos exibir um largo espectro de atividade biológica, incluindo antitumoral, antiviral, antibacteriana e anti-inflamatória, além de ser moduladora do canal de cálcio. 14,15 Na reação de Mannich, a condensação tricomponente de uma cetona enolisável (contendo hidrogênio ácido a à carbonila), formaldeído e amônia, geralmente em meio ácido, fornece como produto um composto b-amino carbonilado 2 (Esquema 2).…”
Section: Introductionunclassified